Peran Guru PAI dalam Menanamkan Sikap Cinta Tanah Air - Oktariani, Cindy; Albina, Meyniar (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to examine the role of Islamic Religious Education (PAI) teachers in instilling the value of patriotism in students. Through observations and interviews with PAI teachers and students, it was found that PAI teachers integrate patriotism values in learning by discussing the struggle of the Indonesian nation in an Islamic perspective, as well as applying storytelling methods, discussions, and creative activities with the theme of nationalism. In addition, teachers also provide examples in showing patriotism, such as by using local products and participating in school activities related to nationalism. Students showed a positive response with an increased sense of pride and the application of patriotism in their daily lives. However, a challenge that arises is the lack of awareness of some students in the digital era. PAI teachers managed to overcome this by providing direct examples and linking the value of patriotism with Islamic teachings.